2020
DOI: 10.1111/jrh.12481
|View full text |Cite
|
Sign up to set email alerts
|

Half of Rural Residents at High Risk of Serious Illness Due to COVID‐19, Creating Stress on Rural Hospitals

Abstract: Purpose During the COVID‐19 epidemic, it is critical to understand how the need for hospital care in rural areas aligns with the capacity across states. Methods We analyzed data from the 2018 Behavioral Risk Factor Surveillance System to estimate the number of adults who have an elevated risk of serious illness if they are infected with coronavirus in metropolitan, micropolitan, and rural areas for each state. Study data included 430,949 survey responses representing over 255.2 million noninstitutionalized US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 12 publications
0
67
0
Order By: Relevance
“…However, mortality may be higher in rural states since older and rural residents are likely to experience greater burden of serious illness and mortality due to COVID-19. 17 Our results may be impacted by measurement error in the outcomes, as asymptomatic cases and out-of-hospital deaths Estimates for excess cases and deaths generated using average marginal effects to compare predicted cases with reopening (before and after implementing mask mandates) compared to not reopening at 6 weeks are likely to be underrepresented. In addition, the state-level data do not capture the variation in local policies, which may have contributed to the impact of reopening.…”
Section: Discussionmentioning
confidence: 95%
“…However, mortality may be higher in rural states since older and rural residents are likely to experience greater burden of serious illness and mortality due to COVID-19. 17 Our results may be impacted by measurement error in the outcomes, as asymptomatic cases and out-of-hospital deaths Estimates for excess cases and deaths generated using average marginal effects to compare predicted cases with reopening (before and after implementing mask mandates) compared to not reopening at 6 weeks are likely to be underrepresented. In addition, the state-level data do not capture the variation in local policies, which may have contributed to the impact of reopening.…”
Section: Discussionmentioning
confidence: 95%
“…This is problematic because individuals in rural locales are more likely to be older, lack health insurance, and have pre-existing medical conditions that increase their risk ( Peters, 2020 ; Razzaghi et al, 2020 ). Due to fewer ventilators, beds, and employees, medical facilities in rural counties are less equipped to handle surges in cases ( Kaufman et al, 2020 ). A subsequent analysis comparing the hospital and reclassified RUCA data revealed that hospitals in counties classified as rural had an average of 0.55 ventilators and 3.39 ICU beds per hospital, while counties classified as urban, micropolitan, and small town had an average of 3.66 ventilators and 14.42 ICU beds per hospital.…”
Section: Discussionmentioning
confidence: 99%
“…During the Covid-19 pandemic, rural communities have the same risk as urban communities. Several studies stated that rural areas have a high risk of Covid-19 transmission 3,4 . Several factors include community characteristics, population mobilization, rural health capacity, government policies and behavior of rural communities as well as the resilience 3,5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…A study in USA stated that the high incidence of Covid-19 in rural areas occurs because of the formation of immunity, symptomless diseases and the spreading of virus very easily and quickly. Hospitals in rural areas also experience a high burden in treating Covid-19 patients 4 . However, more attention is paid to the incidence cases in urban areas 3 .…”
Section: Introductionmentioning
confidence: 99%